Applied Study of Malthusian law of Population Growth; Statistical Comparison in Indian Experience - Nathier Abas Ibrahim (Iraqi Journal for Administrative Sciences, 2025)
India is the countries with ancient civilization and occupies an area of ​​more than 3 million km 2 extends from the Himalayas in the north to the Indian Ocean in the south and called the Indian subcontinent and an area of ​​approximately 2.5% of the area of ​​the world and is home to nearly one sixth of the world's population. During the second half of the last century has increased India's population of approximately 650 million people and this number is the form of growth rate and density of population highs, so the country is needed to reduce the rates of fertility and mortality, noting that the late leader Gandhi was first created a system of birth control in the continent of Asia and the system could not be the state of applied to all members of the community because of the different classes and religions, and the presence of layers and a poor immigrant from one region to another within the country can not be controlled to determine their offspring. Occupies India now second place in the world after China in terms of population, as over 1.03 billion people, and quartz more than sixty years of independence and the application program of birth control has decreased the birth rate of 42 to 28 per 1000 children and accompanied by a decrease in mortality rates and decreased the proportion of males to females by 4% from 1901 to 2001. The Indian society of societies semi-stable, the researchers Biswas & Ebraheem in 1986 tested the hypotheses of this community under the hypothesis of low fertility rates within a planned program with a slight decrease in mortality rates based on the statistics of India for the years 1971 and 1981 Based on hypotheses Coale 1972 communities almost stable. This research is an attempt to test the same hypotheses based on census 2001 and a comparison between the conclusions with some statistics to estimate the coming years.